MODEL MANAJEMEN PONDOK PESANTREN DALAM MENINGKATKAN KEMANDIRIAN SANTRI DI PONDOK PESANTREN HIDAYATUL MUBTADIIN LAMPUNG SELATAN - Nangimah, Milatun (UNISAN JURNAL, 2024)
This study aims to analyze the management model of Islamic boarding schools (pondok pesantren) in enhancing students' (santri) independence. The primary focus of the research is the strategies implemented by the pesantren in building independent character, including aspects of education, skills development, and daily life management of the students. This study employs a qualitative approach with a case study method. Data collection is conducted through direct observation, in-depth interviews with pesantren caregivers, students, and alumni, as well as an analysis of pesantren management policy documentation. The data analysis technique follows the interactive model of Miles and Huberman, involving data reduction, data presentation, and conclusion drawing. The findings indicate that the pesantren applies a management model based on Islamic values that emphasize discipline, responsibility, and self-reliance. The main strategies used include habituation of independent work, student entrepreneurship programs, and a dormitory-based education system that instills discipline and self-reliance in daily life. Supporting factors for the success of this model include the strong role of the kyai and caregivers in setting an example, as well as an educational system that integrates both theoretical learning and direct practice. The effective management model for enhancing students' independence at Pondok Pesantren Hidayatul Mubtadiin combines academic learning, skills training, and character development based on Islamic values. Therefore, this model can serve as a reference for other Islamic educational institutions in shaping independent students who are prepared to face life’s challenges